The Edmonton Symptom Assessment System: A narrative review of a standardized symptom assessment tool in head and neck oncology. (December 2021) - Noel, Christopher W.; Forner, David; Chepeha, Douglas B.; Baran, Elif; Chan, Kelvin K.W.; Parmar, Ambica; Husain, Zain; Karam, Irene; Hallet, Julie; Coburn, Natalie G.; Eskander, Antoine
Graphical abstract: Highlights: Close symptom management is a cornerstone of cancer care. The Edmonton Symptom Assessment System (ESAS) is one of the most commonly used symptom scales in cancer patients across the world. Despite being a generic symptom scale, the ESAS has good discriminative and evaluative properties in a head and neck population. ESAS scores are strongly correlated with emergency department use in head and neck oncology and may be a good tool for risk stratification. Abstract: Objective: Symptom burden is common in head and neck cancer patients though it frequently remains undetected and untreated. The Edmonton Symptom Assessment System - revised version (ESAS-r) is a generic symptom scale deployed in many outpatient settings worldwide. The ESAS-r is meant to improve symptom detection and management. We sought to review the ESAS-r and its psychometric properties in a head and neck oncology population. Methods: Narrative Review. Results: Over the past 30 years, the ESAS-r has emerged as one of the most used symptom scales for cancer patients. Its psychometric properties in a heterogenous cancer population are well supported, proving to be reliable and valid in a variety of settings. The linking of ESAS-r scores with Ontario administrative health data has led to a detailed assessment of validity in head and neck cancer. The ESAS-r can discriminate between high and low levels of symptom burden and is responsive to change over time in this patient population. ESAS-r scores have also been shown to be a strong predictor of future emergency department use and unplanned hospitalization in head and neck cancer patients. Conclusions: The ESAS-r is reliable and valid in the head and neck cancer population and may serve as a useful clinical endpoint in research studies.